“Close but no cigar”: the measurement of corruption - Heywood, Paul M.; Rose, Jonathan (Cambridge University Press, 2014)
The financial cost of corruption has recently been estimated at more than 5 per cent of global GDP. Yet, despite the widespread agreement that corruption is one of the most pressing policy challenges facing world leaders, it remains as widespread today, possibly even more so, as it was when concerted international attention began being devoted to the issue following the end of the Cold War. In reality, we still have a relatively weak understanding of how best to measure corruption and how to develop effective guides to action from such measurement. This paper provides a detailed review of existing approaches to measuring corruption, focusing in particular on perception-based and non- perceptual approaches. We highlight a gap between the conceptualisation of corruption and its measurement, and argue that there is a tension between the demands of policy-makers and anti-corruption activists on the one hand, and the motivations of academic researchers on the other. The search for actionable answers on the part of the former sits uncomfortably with the latter’s focus on the inherent complexity of corruption.